Postcard-TempleOfVandœuvres-ByHirschiEtChristinet-before1921-Bibliothèqu... - Auteur inconnu (Wikimedia Commons, 1920)
Carte postale ancienne issue de Wikimedia Commons. Titre: Postcard-TempleOfVandœuvres-ByHirschiEtChristinet-before1921-BibliothèqueDeGeneveCentreDIconographie. Historical postcard of the protestant church of Vandœuvres in the canton of Geneva, Switzerland. Photo taken before 1921 and published by "Hirschi et Christinet". From the collections of the Bibliothèque de Genève.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église